Pendampingan Pembelajaran Kreatif dengan Metode Project Based Learning di MTs Sunan Drajat Sugihwaras Kalitengah - Khoirun Nisa’; Nashihin Nashihin; Moh. Hafidh Ubaidillah Al Hasan; Mohammad Falahuddin; Eva Ulfiana Dewi; Firdatul Izza (KERIS : Journal of Community Engagement, 2022)
The existence of the corona virus outbreak has hampered teaching and learning activities which usually take place face-to-face. Even so, this pandemic was able to accelerate education 4.0. The learning system is carried out remotely by utilizing information technology. However, there are major challenges in implementing the distance learning model. Project-based learning is a model of learning that is centered on students and provides a meaningful learning experience for students. Students' learning experiences and concepts are built based on the products produced in the project-based learning process. This learning is a method where students have a big role in learning, so in this method students are required to be creative, critical, collaborate, and communicate, this goal is an encouragement to improve the knowledge of the nation's children, when viewed from a global perspective with The sophistication of digitalization which has both positive and negative sides, large possibilities can change the setting of students to be active in learning with their respective capacities, not intending to suppress but to revive the capacity possessed by each student so that it is not monotonous in terms of learning, because each individual must have the ability for himself and others in particular, here also morality is not spared from it because from small things we can make a house in ourselves (willingness) on the other hand we live in the world not only to be silent then what God gives everything to us, if we don't have a move going into doing something